FAKTOR â FAKTOR YANG BERPENGARUH TERHADAP KUNJUNGAN WISATAWAN KE CAGAR ALAM PULAU SEMPU KABUPATEN MALANG PROVINSI JAWA TIMUR - , STEVIE VISTA NISSA ULQODRY, Dr. Ir. Lies Rahayu Wijayanti Faida, M.P. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
N ature Sempu Island Reserve is located in southern part of Java Island precisely in Malang. Sempu Island Nature Reserve is a protected area with limited utilization, nevertheless Sempu Island becomes one of the touristsâ destinations for recreation nowadays. A research upon the factors affecting touristsâ visits is required for suppressing touristsâ visits in Sempu Island Nature Reserve. This research aimed to find out where is the location which becomes touristsâ destination, the characters of tourists, and what does factors affecting touristsâ visit to Sempu Island Nature Reserve. affect This research was held in November 2013 using survey as the method of research and questionnaire as the instrument of research. The sampling was done randomly and used accidental sampling technique. There were 94 respondents as the samples. The result of the research was analyzed descriptively and was supported with diagram of area map and documentation pictures. The analysis employed to find out factors which touristsâ visit was done using analysis factor with the assistance of software SPSS 16.0 for Windows. Touristsâ The researchâs results showed that 1) destination in Sempu Island Nature Reserve mainly was an area of coast with Segara Anakan Lake as the main attraction. 2) The visitors of Sempu Island were dominated by young people. Some activities done by visitors in Sempu Island gave negative impacts to the preservation of area due to peopleâs low awareness towards the importance of preserving the ecosystem. 3) There are four factors which affect touristsâ visit to Sempu Island Nature Reserve: the natural attraction scenery and information availability (26,067%), the accessibility of the area (12,822%), the availability of facility (9,406%), and the availability of public transportation (8,321%).